Ascites in CML: a rare extramedullary manifestation - Bansod, Y. V.; Kharkar, Sandeep V.; Raut, Arshish; Choudalwar, Piyush (International Journal of Research in Medical Sciences, 2017)
Ascites in chronic myeloid leukemia (CML) as an extramedullary manifestation is rarely reported in the literature. A young 23 year old female of chronic myeloid leukemia presenting with extramedullary disease as massive ascites. All stages of granulocytes and a few blasts similar to peripheral blood smear was present in ascitic fluid. Based on clinical symptoms and signs, bone marrow examination, ascitic fluid cytology and ultrasonography of abdomen she was diagnosed as a case of Chronic myeloid leukemia in chronic phase with extramedullary disease as massive ascites. After starting treatment with Imatinib mesylate favourable response was observed.